Calcific Tendinitis of the Supraspinatus Tendon in an Infant. (3rd July 2020) - Wako, Masanori; Ichikawa, Jiro; Koyama, Kensuke; Takayama, Yoshihiro; Haro, Hirotaka
Abstract : Calcific tendinitis of the supraspinatus tendon in adults is common, but it is extremely rare in children. This report presents an unusual case of a 2-year-old boy with calcific tendinitis of the supraspinatus tendon. A mother brought her 2-year-old son to our hospital with a fever and severe left shoulder pain. Examination revealed a temperature of 38.6°C accompanied by a swollen shoulder with extreme pain and restricted movement. The radiographs of his left shoulder showed a large radio-opacity in the subacrominal region, and magnetic resonance imaging showed an elongated T1 and T2 hypointense signal above the supraspinatus tendon. Although these images were suggestive of calcific tendinitis of the supraspinatus tendon, we performed an open biopsy and resection in order to differentiate between a suspected diagnosis of calcific tendinitis, which is incredibly rare within pediatric patients, and infection or a soft tissue tumor. Finally, calcific tendinitis of the supraspinatus tendon was diagnosed by pathologic experiment and successfully treated, with complete resolution of pain and movement. Because only four other pediatric cases of calcific tendinitis of the supraspinatus tendon have ever been reported, there is a lack of information on the diagnostic process, management, and treatment of such a condition in young patients. Calcific tendinitis of the supraspinatus tendon still should be considered when encountering cases with typical findings even if the patient is a child.